Selection of reference genes suitable for normalization of qPCR data under abiotic stresses in bioenergy crop Arundo donax L. - Michele Poli (Nature Portfolio, 2017)
Abstract Suitable reference gene selection in qRT-PCR is a key pre-requisite to produce reliable data in gene expression analyses. In this study, novel primers for six commonly used reference genes (AC1, TLF, Act2, TUB α, EF-1α and GAPDH) plus two new candidates (pDUF221 and RPN6) were designed and comparatively tested for expression stability under abiotic stresses (osmotic, heavy metal and heat shock) in shoot, root and their combination of Arundo donax L., a raising non-food energy crop. Expression stability rankings from the most to the least stable gene in each condition and in two tissues (young shoots and roots) were generated with geNorm, NormFinder and BestKeeper programs. All programs provided similar rankings and, strikingly, in most cases identified one of the new candidates, RPN6, as the most suitable reference gene. This novel set of reliable references allows to choose either the best combination of reference genes across multiple stress/organ conditions or to select condition-specific genes that can improve the quality of qRT-PCR analysis. This work provides a solid basis for the functional characterization of A. donax, by enabling accurate quantification of the transcriptional responsiveness under a series of common stress conditions of any gene of interest in this promising biomass/bioenergy species.